Implementation Strategies and Performance of Non-Governmental Organization Projects in Rwanda: A Case of Faith Victory Association Projects, Kayonza District - Kwizera, Bosco N.; Munene, Paul (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The general objective of this  study is to assess the  effect of implementation strategies on performance of NGO projects with specific reference to Gikuriro project implemented by Faith Victory Association in Kayonza.The specific objectives were to examine the community empowerment ,capacity building and community participation on performance of NGO projects.The study played a significant role to various people including researcher, the management of the project itself, government and academic researchers.When conducting this study, a descriptive research design with two mixed methods such as quantitative and qualitative approach was used.The target population were project beneficiaries who were given questionnaires and the project administrators as well as staff who were interviewied. In total the total target population was 13250 people, from whom a sample of 400 were selected USING  Sloven’s formula.The study used a stratified random sampling technique and data were collected using questionnaires and interviews.The analysis of data was done using SPSS version 22.0 and Microsoft Excel.  Both inferential (correlation and regression analysis)and descriptive statistics(mean and standard deviation) were used. The findings pertaining research objectives showed that the community empowerment, capacity building and community participation affect performance of NGO projects. On community empowerment 95% of the respondents Community training, Farmer learning schools, Village Nutrition Schools as capacity building startegy affected performance of NGO projects. The study findings  further showed that  89% of respondents agreed that community empowermnt  through saving groups affected performance of NGO projects.The study findings showed  the community participation in utilities or consumable agriculture products  was 61%.  animal assets was24% in agricultural tools represent 47% while in house and land assets 54.8%. When assessing the relationship between implementation strategies and performance of NGO projects with specific reference to Gikuriro project implemented by Faith Victory Association in Kayonza, the study findings showed that  there is a significant relationship between implementation strategies and performance of NGO projects which presented a positive correlation with p-value (r = 0.092, p = 0.067), (r = -0.008, p = 0.000), (r = 0.016, p = 0.000), (r = 0.042, p = 0.000), (r = 0.006. p = 0.000) and (r = -0.036, p = 0.000).  The study concludes that community empowermnnt, Capacity building and community participation on performance of NGO projects are important satrategies for ensuring project sustainability. The study, recommended that NGO  funded projects  in Kayonza District should be having  clear guiding implementation strategies and  procedure,  community  participation strategy  in place and integrating monitoring in their implementation strategies  at all stages.